Radioprotective Effects of Melatonin on Bone Marrow Cells in Total Body Irradiated Mice - Kaplan, Bunyamin; Eroglu, Celalettin; Ozkul, Yusuf; Halici, Mehmet (Asian Journal of Chemistry, 2011)
This study was undertaken to evaluate the radioprotective effects of melatonin (N-acetyl-5- methyloxy tryptamine) in total body irradiated mice. Albino mice were intraperitoneally (i.p.) treated with 5 or 25 mg/kg melatonin, either 0.5 h before or 0.5 h after exposure to 200 cGy whole body irradiation using a 60Co g-irradiation machine. The animals were divided into six groups. Each group was subdivided equally, half processed for micronuclei examination and the other subgroup was processed for mitotic index assay. All mice were sacrificed 24 h following treatment. The incidence of micronuclei formation and mitotic index in these bone marrow cells (BMCs) were determined for all groups. The results showed that melatonin caused a significant reduction in micronuclei formation and mitotic index of bone marrow cells depending of the melatonin dose and administration time. Administration of one single 25 mg/kg melatonin dose given before irradiation, reduced bone marrow cell mitotic index and micronuclei formation significantly (p < 0.05). However, no significant effect was observed when melatonin was given after irradiation. The data obtained from this study indicated that melatonin administration may have an active role in protection against damage inflicted by radiation when given prior to exposure to irradiation and not after, depending on it's dosage.